2015
DOI: 10.12803/sjseco.4712315
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Welfare Facilities in the Workplace: Issues in Perspectives

Abstract: Prishtina Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The current study found a statistically significant relationship between these two constructs. This outcome was consistent with other business management research which reported that there was a direct positive relationship between welfare facilities and EWM (Odeku & Odeku, 2015). The findings of the present study evidenced a significant relationship between welfare facilities and EWM.…”
Section: Discussion Of the Findingssupporting
confidence: 93%
“…The current study found a statistically significant relationship between these two constructs. This outcome was consistent with other business management research which reported that there was a direct positive relationship between welfare facilities and EWM (Odeku & Odeku, 2015). The findings of the present study evidenced a significant relationship between welfare facilities and EWM.…”
Section: Discussion Of the Findingssupporting
confidence: 93%
“…The derived regression model (Model 3) explained that employee welfare has a positive and significant relationship with CER. In many studies, it has been theoretically established that the welfare measures offered by the organization aim at keeping employees satisfied and inducing a strong employer–employee relations (Logasakthi & Rajagopal, 2013; Nanda & Panda, 2013; Odeku & Odeku, 2015; Satyanarayana, 2010; Yadav & Kumar, 2013). Sindhu (2012) conducted a study on the hypothesized relationship and conferred a similar finding.…”
Section: Discussionmentioning
confidence: 99%
“…The extramural (outside establishment) facilities comprise housing, educational, medical, recreation club, transportation and so on which are availed by both the employees and their families. The welfare measures are the means to happiness of the employees and enhance motivation (Odeku & Odeku, 2015; Ramana & Reddy, 2015) morale, job satisfaction, employee involvement (Upadhyay & Gupta, 2012), retention, employee health, living standard (Mohan & Panwar, 2013), job performance, efficiency, productivity, employee creativity, industrial peace (Kemboi et al, 2013; Logasakthi & Rajagopal, 2013; Sindhu, 2012) and quality of work-life (Satyanarayana, 2010). It acts as a stimulus for employees’ dedication and efficiency in the organization (Casey, 1999; Tiwari, 2014).…”
Section: Overview Of Literature and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation